The Future of Work and Consumption in Cities after the Pandemic: Evidence from Germany - Jean-Victor Alipour; Oliver Falck; Simon Krause; Carla Krolage; Sebastian Wichert (Center for Economic Studies and ifo Institute (CESifo), 2022)
We estimate the impact of Covid-induced working from home (WFH) on offline consumer spending in urban agglomerations. Our analysis draws on postcode-level data on card transactions and WFH patterns in major German cities between January 2019 and May 2022. We address endogeneity in WFH uptake by estimating intention-to-treat effects based on "untapped WFH potential", i.e. the share of employees with a teleworkable job who did not WFH pre-pandemic. This measure approximates the local scope to expand WFH and explains both observed WFH growth during the pandemic as well as prospective employer plans and employee desires. Difference-in-differences estimates show that local spending increases by 2–3 percent per standard deviation higher untapped WFH potential. The effects are only significant in non-lockdown periods and after Covid restrictions are permanently lifted. Null effects during lockdowns are consistent with temporary shifts toward online spending when business closures preclude regional relocation of offline consumption.
Keywords: D10; E20; G20; J00; 330; Covid-19; geography of consumption; consumer spending; work from home; Germany